Meaningful vectors of Uzbek story at the turn of XX-XXI centuries - Egamberdieva H.M., Kamilova Saodat Ergashevna, Boltabaeva A.M., Alimova N.H. (Opción, 2020)
This article reveals the originality of the status relationship between the author, narrator and protagonist in the Uzbek story of the turn of the XX-XXI centuries through the prism of the problem and thematic fields of flash fiction of Uzbekistan. Three substantial vectors of the Uzbek story of the period under study are distinguished. The analysis of stories from these angles allows not only to show originality of development of a genre of the Uzbek story, but also to reveal a spectrum of the problems fixed by the story the end of XX - the beginning of XXI centuries reflecting a true picture of a human existence of the given period.